Tracking the turfgrass literature: Growth and evolution. Issue 1 (19th March 2021) - Lundeen, Andrew; Cookingham, Peter O.
Abstract: Beginning in the late 19th century the literature of turfgrass science and management began to grow, paralleling the rise of scientific reporting beginning around the turn of the century. While most of the literature produced prior to the 1920s was monographic in nature, the 1921 introduction of the Bulletin of the Green Section of the U.S. Golf Association coincided with an explosion in the serial literature, which has dominated the subsequent century of published communications. Slowdowns and declines due to the Great Depression and Second World War were followed by the rapid expansion of print reporting, with specific categories such as conference proceedings rising and then falling in significance. Other types of publications have followed different patterns of growth, such as turfgrass theses and dissertations, which appear to be fairly stable as a percentage of the total literature since the 1960s. An era of explosive growth, particularly within the trade and professional literature, began in the late 1980s and peaked around 2010, followed by a substantial decline in reporting that appears to be continuing.